Edward F. Adolph Distinguished Lecture. Age and sex differences in the limits of human performance: fatigability and real-world data - Hunter, S. K. (Journal of Applied Physiology, 2024)
High-level athletic performances may be a proxy for the trajectory of optimal function of human biology with advanced aging and the differences between males and females. Males are faster, stronger, and more powerful than females and these physical attributes decline dramatically with advanced aging for both sexes. Experimental mechanistic studies determine the physiological mechanisms for these sex and age differences in human physical performance. The assumption however, that real-world performances solely reflect the biological and physiological differences between the sexes and with advanced aging, even among elite athletes, is not complete. This review presents evidence that an integrated approach encompassing analysis of real-world data and experimental mechanistic studies is necessary to determine the biological and sociocultural factors attributed to the limits of performance with aging and between males and females. First, experimental studies are presented that focus on the sex and age differences in performance fatigability that determine the physiological mechanisms of absolute and relative exercise performance. Second, analysis of current and historical real-world data including world records, and performances of elite, collegiate, and competitive age-group athletes are highlighted. These data illustrate that the upper limits of physical performance that have changed historically, and other factors such as sociocultural influences, explain the widening of the sex and age gaps in human performance observed in real-world data even in present-day performances. These approaches have broader significance when applied to understanding the impact of the historically low representation of females and minority groups in biomedical research on health outcomes.